Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1016/j.yjmcc.2010.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel accelerates spontaneous calcium oscillations in cardiomyocytes by interacting with NCS-1 and the InsP3R

Abstract: Paclitaxel (Taxol) is a microtubule-stabilizing compound that is used for cancer chemotherapy. However, Taxol administration is limited by serious side effects including cardiac arrhythmia, which cannot be explained by its microtubule-stabilizing effect. Recently, neuronal calcium sensor 1 (NCS-1), a calcium binding protein that modulates the inositol-1,4,5-trisphosphate receptor (InsP 3 R), was described as a binding partner of Taxol and as a substrate of calpain. We examined calcium signaling processes in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 28 publications
(44 reference statements)
2
43
0
2
Order By: Relevance
“…This finding is consistent with those of previous reports that have demonstrated that NCS-1 enhances IP 3 R activity when monitored as the activity of single channels and as Ca 2ϩ transients in intact cells. 23,25 In addition, the present experiments using the overexpression system were able to directly demonstrate that IP 3 R activation results in CaMKII-␦ phosphorylation, and this was further enhanced by NCS-1 overexpression ( Figures 7C and 7D), which supports a functional link between NCS-1, IP 3 R, and CaMKII activation. The present experiments showed that CaMKII-␦ and NCS-1, which were overexpressed in HEK293 cells, did not coimmunoprecipitate or colocalize with each other (Online Figure VI), which rules out possible direct interactions between NCS-1 and CaMKII-␦ independent of the effects of NCS-1 on IP 3 R. Taken together, these results suggest that NCS-1-IP 3 R interactions could serve as a Ca 2ϩ source for the activation of CaMKII, leading to a higher rate of SR Ca 2ϩ pumping and release and inducing global Ca 2ϩ signaling, thus promoting EC coupling in immature hearts (Online Figure VII depicts a possible signaling pathway).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This finding is consistent with those of previous reports that have demonstrated that NCS-1 enhances IP 3 R activity when monitored as the activity of single channels and as Ca 2ϩ transients in intact cells. 23,25 In addition, the present experiments using the overexpression system were able to directly demonstrate that IP 3 R activation results in CaMKII-␦ phosphorylation, and this was further enhanced by NCS-1 overexpression ( Figures 7C and 7D), which supports a functional link between NCS-1, IP 3 R, and CaMKII activation. The present experiments showed that CaMKII-␦ and NCS-1, which were overexpressed in HEK293 cells, did not coimmunoprecipitate or colocalize with each other (Online Figure VI), which rules out possible direct interactions between NCS-1 and CaMKII-␦ independent of the effects of NCS-1 on IP 3 R. Taken together, these results suggest that NCS-1-IP 3 R interactions could serve as a Ca 2ϩ source for the activation of CaMKII, leading to a higher rate of SR Ca 2ϩ pumping and release and inducing global Ca 2ϩ signaling, thus promoting EC coupling in immature hearts (Online Figure VII depicts a possible signaling pathway).…”
Section: Discussionsupporting
confidence: 74%
“…22 Recently, NCS-1 was reported to be involved in paclitaxel-induced spontaneous Ca 2ϩ oscillation in cardiomyocytes. 23 However, little evidence is available for its physiological and pathological roles in cardiac functions, possibly because of its relatively low expression in the adult heart. We previously detected high expression levels (comparable to the levels in neurons) of NCS-1 in immature hearts 17 and hypertrophic hearts overexpressing Na ϩ /H ϩ exchanger 24 (data not shown); therefore, we hypothesized that NCS-1 has a specific role in cardiac function, particularly at the immature stage and during progression of hypertrophy.…”
mentioning
confidence: 99%
“…In neonatal rat ventricular myocytes, paclitaxel accelerated spontaneous oscillatory changes in cytosolic Ca 2+ by interacting with InsP3R. 20 The effect of paclitaxel on mPTP was not blocked by the inhibiter of InsP3R in this study. Ca 2+ -releasing channels from the SR are different between neonatal and adult ventricular myocytes, and Ca 2+ release by InsP3R is not dominant in adult ventricular myocytes.…”
Section: Stabilization Of Mts and Mptpmentioning
confidence: 42%
“…19 In neonatal cardiomyocytes, paclitaxel accelerates spontaneous Ca 2+ oscillations via InsP3R. 20 Thus, we investigated whether paclitaxel-induced mPTP opening was dependent on InsP3R. For this purpose, 2-aminoethoxydiphenyl borate (2-APB; 20 μmol/L), a blocker of InsP3R, was used.…”
Section: Cell Culture and Transfections Of H9c2 Cellsmentioning
confidence: 99%
“…Here, we found that pretreatment with taxol completely stabilized microtubules in mouse islets, inhibited insulin secretion induced by KCl, tolbutamide, or glucose, but also attenuated the rise in [Ca 2ϩ ] c produced by the three secretagogues. Microtubuleindependent effects of taxol on Ca 2ϩ release from the endoplasmic reticulum have been described in neural cells and cardiomyocytes (3,62), but we are not aware of effects on voltage-dependent calcium channels. Whatever the underlying mechanism, the small decrease of [Ca 2ϩ ] c pro- duced by taxol probably contributed to the partial inhibition of secretion.…”
Section: Discussionmentioning
confidence: 96%